Adult Recollections of Childhood Memories: What Details can be Recalled?. Issue 7 (July 2014) - Wells, Christine; Morrison, Catriona M.; Conway, Martin A.
In a memory survey, adult respondents recalled, dated, and described two earliest positive and negative memories that they were highly confident were memories. They then answered a series of questions that focused on memory details such as clothing, duration, weather, and so on. Few differences were found between positive and negative memories, which on average had 4/5 details and dated to the age of 6/6.5 years. Memory for details about activity, location, and who was present was good; memory for all other details was poorer or at floor. Taken together, these findings indicate that (full) earliest memories may be considerably later than previously thought and that they rarely contain the sort of specific details targeted by professional investigators. The resulting normative profile of memory details reported here can be used to evaluate overly specific childhood autobiographical memories and to identify memory details with a low probability of recall.